Learning Interest of Vietnamese University Students in the Context of Digital Transformation - Le Thi Quynh Trang (CV. Pusdikra Mitra Jaya, 2026)
This study investigates the learning interest of Vietnamese university students in the context of digital transformation, using a mixed-methods approach that combines quantitative surveys and in-depth interviews. Data were collected from students across multiple disciplines to examine factors influencing learning interest, including personal characteristics, learning environment, and social-professional support. Results indicate that students demonstrate a relatively high level of learning interest, with female students, senior-year students, and social sciences majors showing higher engagement. Digital transformation, particularly interactive teaching methods, e-learning platforms, and experiential learning activities, significantly enhances students’ motivation and active participation. The study highlights the critical role of self-directed learning, intrinsic motivation, and support from instructors and peers. Practical implications for educators, universities, and policymakers are discussed, while the research also contributes to theoretical understanding by integrating personal, environmental, and social factors influencing learning interest in digitalized higher education. Limitations include sample scope and reliance on self-reported data, suggesting directions for future research using larger samples and learning analytics.